Partially Purified Extracts of Sea Anemone Anemonia viridis Affect the Growth and Viability of Selected Tumour Cell Lines. (20th September 2016) - Bulati, Matteo; Longo, Alessandra; Masullo, Tiziana; Vlah, Sara; Bennici, Carmelo; Bonura, Angela; Salamone, Monica; Tagliavia, Marcello; Nicosia, Aldo; Mazzola, Salvatore; Colombo, Paolo; Cuttitta, Angela
Abstract : In the last few years, marine species have been investigated for the presence of natural products with anticancer activity. Using reversed phase chromatography, low molecular weight proteins were fractionated from the sea anemone Anemonia viridis . Four different fractions were evaluated for their cytotoxic activity by means of erythrocyte haemolysis test, MTS, and LDH assays. Finally, the antiproliferative activities of three of these fractions were studied on PC3, PLC/PRF/5, and A375 human cancer cell lines. Our analysis revealed that the four fractions showed different protein contents and diverse patterns of activity towards human PBMC and cancer cell lines. Interestingly, fractions III and IV exerted cytotoxic effects on human cells. Conversely, fractions I and II displayed very low toxic effects associated with antiproliferative activities on cancer cell lines.